Analisis Nilai-Nilai Pendidikan Kewirausahaan Melalui Program Market Day Di Sekolah Alam Bangka Belitung - Khoirunnisa, Serin; Diana Pramesti; Erika Fitri Wardani (Universitas Muhammadiyah Bangka Belitung, 2025)
This study aims to determine the entrepreneurial values of the market day program activities carried out at Sekolah Alam Bangka Belitung. This research uses descriptive qualitative method. Data were collected through observations and interviews conducted with fourth grade teachers and 11 students. Data analysis was done through data reduction, data presentation, and conclusion drawing. The results of the research analyzed entrepreneurial values in the activities of the market day program which is carried out regularly once a week on Friday. Students are taught to prepare everything from making products to marketing products in market day activities. The entrepreneurial values resulting from the market day program activities carried out at Sekolah Alam Bangka Belitung from 11 students interviewed, the most dominant of which emerged were the value of taking risks seen when students were ready and brave enough to maintain the rules in the market day; action-oriented value seen when students feel happy if they participate in market day activities; and leadership value seen when students can act decisively to friends who break the rules in market day program activities.